ANALYSIS OF FACTORS AFFECTING UNDERPRICING IN COMPANIES CONDUCTING INITIAL PUBLIC OFFERINGS - Sunarko, Calista Sanko; Rasyid, Rosmita (Graduate Program of Universitas Tarumanagara, 2023)
The aim of this study was to collect empirical evidence on the effects of return on assets, financial leverage, earnings per share, offering percentage, and company age toward underpricing on Companies listed Initial Public Offering (IPO) on the Indonesian Stock Exchange (IDX) for the period 2017-2020. The total number of samples used was 17 samples, selected by sampling method. purposeful sample. The data processing techniques used multiple regression analysis and were processed by SPSS 25. The outcomes of this study show that return on assets has a significant positive impact on underpricing, while offering percentage has a significant negative impact on underpricing. Other variables (financial leverage, earnings per share, and age of the company) had no impact on underpricing.